Exploring the Deep Marine Biosphere: Challenges, Innovations, and Opportunities - Cario, Anaïs; Oliver, Gina C.; Rogers, Karyn L. (Frontiers in Earth Science, 2019)
The deep marine biosphere is one of the largest, and yet least explored, microbial habitats on the planet. Quantifying the extent, diversity, and activity of subsurface microbial communities is a crucial part of understanding their role in global biogeochemical cycles. Even though deep biosphere habitats can vary widely in chemistry, temperature, turnover rates, and energy sources, all subsurface microbes inherently experience high pressures. While not all subsurface microbes require elevated pressures, for many high pressures are essential to their cellular function and metabolism. Thus, when targeting this elusive portion of the biosphere, it is critical to maintain in situ pressure while sampling and cultivating subsurface microorganisms. In this perspective paper we highlight the sampling and cultivation technologies available to study these communities under in situ conditions. Maintaining elevated pressures throughout sampling, transfer, cultivation, and isolation is challenging, and more often than not samples are decompressed at some point during sample handling, potentially leading to biases in both community diversity and isolate physiology. The development of devices that maintain in situ pressures during sampling and allow for sample transfer without decompression have begun to address this challenge. Such vessels can be used for both retrieval and enrichment of deep subsurface samples, as well as high-pressure growth and physiology experiments, thus expanding possibilities for deep biosphere exploration. Finally, we discuss the significant need to develop and share high-pressure facilities across the deep biosphere community, in order to expand the opportunities to discover novel piezophiles from the deep subsurface.